ChemInform Abstract: Investigation of a Naked Ag7 Cluster: Configurations and Spectral Characteristics. Issue 27 (18th June 2015) - Xu, Shuhong; Wang, Zhaochong; Wang, Chunlei; Wang, Zhuyuan; Cui, Yiping
Abstract DFT calculations show that the most stable Ag7 cluster is a pentagonal bipyramid, whereas synthesized Ag7 clusters are planar due to interactions with ligands as revealed by Raman and UV/VIS spectroscopy.